English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

this is a test question, and if you could send me the workings that would be great.

2006-06-05 13:05:28 · 3 answers · asked by V 2 in Science & Mathematics Mathematics

3 answers

nb2718 is almost correct except for one thing:

d/dx (-x^2 + 2) = -2x Where did that minus sign go?? That'd cost you 5 points on a test, or it would have with my calculus teacher!

f(x + h) = -(x +h)^2 + 2 = -[x^2 + 2xh + h^2]+2

f(x) = (-x^2 + 2)

lim h-->0 {[-x^2 - 2xh -h^2] + 2 - [(-x^2 + 2)]}/h =

lim h-->0 {-x^2 - 2xh -h^2 + 2 + x^2 - 2}/h =

lim h-->0 {h(-2x + h)/h} now divide by h before it goes to zero...

lim h--> {-2x + h} = -2x

QED

2006-06-05 14:24:17 · answer #1 · answered by cat_lover 4 · 0 0

by definition, the derivative is (f(x+h) - f(x))/h as h approaches 0. So just substitute:

f(x+h) = (x+h)² + 2 = x² +2xh + h² +2, so

((x² +2xh + h² + 2) - (x² + 2))/h = (2xh + h²)/h

= 2x + h. And the limit of that as h goes to 0 is 2x.

2006-06-05 13:23:02 · answer #2 · answered by Anonymous · 0 0

The derivative of a function is defined based on how the function changes with respect to x, and this change is represented by its gradient as x changes.

f(x) = (-x)^2 + 2
f'(x) = -2x

2006-06-05 17:05:27 · answer #3 · answered by Kemmy 6 · 0 0

fedest.com, questions and answers